The Effect of Inflation and Economic Growth on Return on Asset (ROA) of Sharia Banks In Indonesia - Marsha Meira Albania; Haqiqi Rafsanjani; Rifa'atul Maftuhah (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2025)
The purpose of this study is to examine how inflation and economic expansion affect Indonesian Islamic banks' return on assets (ROA). Time series data from the Central Statistics Agency (BPS), Bank Indonesia, and the Financial Services Authority (OJK) from 2014 to 2023 are used in this analysis. The Vector Error Correction Model (VECM), VECM Estimation, IRF and VD, Stationarity Test, Optimal Lag Test, Stability Test, Cointegration Test, Causality Test are the analysis method employed. With trace statistics and significant, the study's findings indicate a long-term link between the variables according to the Johansen cointegration test. According to the VECM results, economic growth has a positive impact on ROA, while inflation has a negative effect. However, neither effect is statistically significant in the short run. According to IRF research, inflation's effect on ROA is first erratic but eventually tends to be neutral. VD demonstrates that internal factors have a greater impact on ROA fluctuation than either inflation or economic growth.